Increased Mucosal Thrombin is Associated with Crohn's Disease and Causes Inflammatory Damage through Protease-activated Receptors Activation. (17th November 2020) - Motta, Jean-Paul; Palese, Simone; Giorgio, Carmine; Chapman, Kevin; Denadai-Souza, Alexandre; Rousset, Perrine; Sagnat, David; Guiraud, Laura; Edir, Anissa; Seguy, Carine; Alric, Laurent; Bonnet, Delphine; et al.
Abstract: Background and Aims: Thrombin levels in the colon of Crohn's disease patients have recently been found to be elevated 100-fold compared with healthy controls. Our aim was to determine whether and how dysregulated thrombin activity could contribute to local tissue malfunctions associated with Crohn's disease. Methods: Thrombin activity was studied in tissues from Crohn's disease patients and healthy controls. Intracolonic administration of thrombin to wild-type or protease-activated receptor-deficient mice was used to assess the effects and mechanisms of local thrombin upregulation. Colitis was induced in rats and mice by the intracolonic administration of trinitrobenzene sulphonic acid. Results: Active forms of thrombin were increased in Crohn's disease patient tissues. Elevated thrombin expression and activity were associated with intestinal epithelial cells. Increased thrombin activity and expression were also a feature of experimental colitis in rats. Colonic exposure to doses of active thrombin comparable to what is found in inflammatory bowel disease tissues caused mucosal damage and tissue dysfunctions in mice, through a mechanism involving both protease-activated receptors -1 and -4. Intracolonic administration of the thrombin inhibitor dabigatran, as well as inhibition of protease-activated receptor-1, prevented trinitrobenzene sulphonic acid-induced colitis in rodent models. Conclusions: Our data demonstrated that increased local thrombin activity, as it occurs in the colon of patients with inflammatory bowel disease, causes mucosal damage and inflammation. Colonic thrombin and protease-activated receptor-1 appear as possible mechanisms involved in mucosal damage and loss of function and therefore represent potential therapeutic targets for treating inflammatory bowel disease.